Molecular characterisation and expression analysis of cathepsin D from the Asian seabass lates calcarifer - Shariza Azizan,; Kiew, Lian Wan; Adura Mohd-Adnan, (Universiti Kebangsaan Malaysia, 2014)
The lysosomal aspartic proteinase cathepsin D is an acute phase protein involved in various physiological processes, including vitellogenesis, yolk processing and immune responses. In this study, we characterised the cathepsin D from the Asian seabass Lates calcarifer and examined its expression profile during infection. The complete coding sequence of L. calcarifer cathepsin D consists of 1191 nucleotides, encoding a 396 amino acid protein molecule that is made up of a putative signal peptide, a leader peptide and a mature peptide. Phylogenetic analyses showed that two types of cathepsin D are present in the teleost lineage i.e. cathepsin D1 and D2, whereas higher vertebrates possess only one type of cathepsin D. L. calcarifer cathepsin D was clustered together with cathepsin D1 from other teleosts. Compared to mammalian sequences, L. calcarifer cathepsin D lacks the β-hairpin loop that forms the double chain and is present as a single chain peptide with conserved aspartic active sites like other fish. Both multiple sequence alignment and phylogenetic analysis indicated that the L. calcarifer cathepsin D sequence codes for cathepsin D1 and suggested that it shares the same functions with cathepsin D from other fish. Expression profiling analysis of cathepsin D in L. calcarifer infected with Aeromonas hydrophila showed that it is up-regulated in immune-related tissues such as gills, spleen and liver, suggesting that cathepsin D plays an important role in the innate immune response of L. calcarifer against pathogens.